Religious Coping, Hopelessness, and Suicide Ideation in Subjects with First-Episode Major Depression: An Exploratory Study in the Real World Clinical Practice - Domenico De Berardis (Brain Sciences, 2020)
Background. This study aimed to evaluate the potential relationships between religious coping, hopelessness, and suicide ideation in adult outpatients with the first episode of major depressive disorder (MDD). Methods. Ninety-four adult outpatients with MDD were assessed through the Hamilton Depression Rating Scale (HAM-D), the Beck Hopelessness Scale (BHS), and the Scale of Suicide Ideation (SSI). Religious coping was assessed with the Italian version of the Brief RCOPE scale, consisting of seven positive coping items (PosCop) and seven negative coping items (NegCop). Results. The results showed that the Brief RCOPE PosCop scale exhibited a strong inverse correlation with HAM-D, BHS, and SSI, whereas HAM-D and BHS were positively correlated with SSI. Brief RCOPE NegCop scores were positively correlated only with SSI. Regression analysis with SSI as the dependent variable showed that higher Brief RCOPE PosCop scores were associated with lower suicide ideation, whereas higher HAM-D and BHS scores were associated with higher suicide ideation. Conclusion. Positive religious coping may be a protective factor against the development of suicide ideation, perhaps counteracting the severity of depressive symptoms and hopelessness. The evaluation of religious coping should be performed in all subjects with MDD in everyday clinical practice. However, this study was preliminary, and limitations must be considered.